Alaska Mercantile Company's warehouses and main store, Nome, October 1, 1906 - Nowell, Frank H., 1864-1950 (1906)
Caption on image: Rear view of Alaska Mercantile Co's warehouses 4, 5, 6, and main store, Nome, Alaska, Oct. 1st 1906. F.H. Nowell, 5266 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number